Keterlibatan dan Pola Pergerakan Teroris Perempuan dalam Jaringan Terorisme di Indonesia - Jodi Quanandi; Susaningtyas N.H. Kertopati; Fauzia Gustarina Cempaka Timur (Mahesa Research Center, 2022)
This article aims to analyze analytically the processes that influence the involvement of women in acts of terrorism in Indonesia. The problem is focused on the case of suicide bombings with female terrorist actors who are often with terrorist networks and received news coverage by various media describing the pattern of relationships between the influence of religious concepts, action orientation and patriarchal domination in Indonesian society. To approach this problem, theoretical references and literature studies from previous journals are used. The data were collected and analyzed descriptively qualitatively. The results of this study indicate that the data on women who participated in acts of terrorism and also know the factors that influence women's participation in acts of terrorism carried out through suicide bombings, one of which is the Jamaah Ansharut Daulah network which is suspected to be affiliated with ISIS. This study also elaborates on the extent to which women's involvement in suicide cases is determined by how they interpret jihad and the orientation of their actions as well as the domination of the patriarchy that surrounds them and their pattern of movement in supporting terrorist acts.